The Urgency of Counseling Guidance Instrumentation in Supporting Student Learning Success - Ade Bagus Suponco; Khairuddin Tambusai (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study was to determine how counseling (BK) instrumentation affects students' academic success at MAN 1 Southeast Aceh. Counselors and students from the same school acted as research subjects. This study presents findings and reveals facts using qualitative methods. According to the research findings, the application of BK instrumentation facilitates special guidance and counseling services for students. To meet students' needs, the data available in BK instrumentation is intended to streamline and optimize the provision of counseling services. Student learning outcomes have an overall average score of 81.21, with the highest score of 85.65 and the lowest of 78.50, indicating good academic performance. This indicates that the use of BK instrumentation effectively improves students' academic performance at MAN 1 Southeast Aceh and contributes to the success of various counseling services.